2016
DOI: 10.1038/nutd.2016.23
|View full text |Cite
|
Sign up to set email alerts
|

Associations of anthropometric markers with serum metabolites using a targeted metabolomics approach: results of the EPIC-potsdam study

Abstract: Background/Objectives:The metabolic consequences of type of body shape need further exploration. Whereas accumulation of body mass in the abdominal area is a well-established metabolic risk factor, accumulation in the gluteofemoral area is controversially debated. We evaluated the associations of anthropometric markers of overall body mass and body shape with 127 serum metabolites within a sub-sample of the European Prospective Investigation into Cancer and Nutrition (EPIC)-Potsdam cohort.Subjects/Methods:The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 56 publications
2
46
0
Order By: Relevance
“…The method of Absolute IDQ TM p150 Kit has been proven to be in conformance with the EMEA-Guideline “Guideline on bioanalytical method validation (July 21st 2011”) [26], which implies proof of reproducibility within a given error range. A detailed description of the sample preparation, assay procedures and nomenclature have been published previously [27-29]. …”
Section: Methodsmentioning
confidence: 99%
“…The method of Absolute IDQ TM p150 Kit has been proven to be in conformance with the EMEA-Guideline “Guideline on bioanalytical method validation (July 21st 2011”) [26], which implies proof of reproducibility within a given error range. A detailed description of the sample preparation, assay procedures and nomenclature have been published previously [27-29]. …”
Section: Methodsmentioning
confidence: 99%
“…Many studies have used metabolomic profiling to identify metabolites and metabolic pathways that are altered in individuals with overweight and obesity. These include several smaller studies (10 to 140 participants) that compared metabolite levels in groups of adults defined by body size measures , as well as studies with larger sample sizes derived from a specific population or prospective cohort studies . Collectively, these studies have found that levels of several amino acids, including the branched chain amino acids (BCAAs) leucine, isoleucine, and valine, are higher in obesity, whereas other amino acids are lower .…”
Section: Introductionmentioning
confidence: 99%
“…These include several smaller studies (10 to 140 participants) that compared metabolite levels in groups of adults defined by body size measures , as well as studies with larger sample sizes derived from a specific population or prospective cohort studies . Collectively, these studies have found that levels of several amino acids, including the branched chain amino acids (BCAAs) leucine, isoleucine, and valine, are higher in obesity, whereas other amino acids are lower . Numerous lipids, including fatty acids (FAs), glycerophospholipids, and sphingolipids , as well as the carbohydrates glucose and mannose , are also perturbed with obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now possible to detect and identify thousands of metabolites in a single run [1,2,3]. Although, initially, metabolomics had been applied mostly as a data-driven hypothesis generating approach in an un-targeted manner, recently both targeted and un-targeted metabolomics are becoming more popular to resolve many research questions [3,4,5,6]. Among different techniques of metabolite analysis, metabolite profiling is the oldest and most widely used in life sciences, and focuses on the study of a large group of metabolites related to different metabolic pathways [7].…”
Section: Introductionmentioning
confidence: 99%